C3 glomerulonephritis in Cape Town, South Africa - a case series - Hargey, Irfaan; Coetzee, Liezel; Bates, William; Chothia, Mogamat-Yazied (African Journal of Nephrology, 2023)
Background C3 glomerulonephritis (C3GN) is a rare disease of the alternative complement pathway and is associated with poor kidney and patient outcomes. There are no studies from sub-Saharan Africa. We aimed to identify the incidence, describe the clinical features, and report on the time to the composite outcome of CKD, ESKD or death following kidney biopsy. Methods A retrospective cohort study of all adult patients with a kidney biopsy-confirmed diagnosis of C3GN was performed at our tertiary centre in Cape Town, South Africa, over a 16-year period. C3GN was defined as exclusive C3 positivity or a C3 stain of two orders of magnitude greater than any other immune reactant on immunofluorescence. Kaplan-Meier survival analysis was performed for the composite outcome. Results A total of 19 patients with C3GN were identified with an estimated incidence rate of 0.9 per million population per year. The composite outcome occurred in 79% (n=15) with a median survival probability of 25 months. The median age was 31 (IQR 24-45) years, most were male (79%) and 58% were hypertensive. Three quarters presented with nephritic-nephrotic syndrome. At the time of biopsy, the median creatinine was 212 (IQR 134-752) µmol/L, estimated glomerular filtration rate 33 (IQR 8-65) mL/min/1.73 m2, proteinuria of 5.8 (IQR 5-10) g/day and low C3 in 53%. Conclusion This is a first description of C3GN from sub-Saharan Africa. Overall prognosis was very poor which may be due to late presentation.